1965
DOI: 10.23986/afsci.71621
|View full text |Cite
|
Sign up to set email alerts
|

Certain parasites of fungal sclerotia

Abstract: Rhizopus nigricans EHRENB., Sporotrichum carnis Brooks & Hansford, Coniothyrium minitans CAMPB. (two isolates) and Acrostalagmus roseus BAINIER proved to infect sclerotia of Sclerotinia trifoliorum, S. sclerotiorum and Botrytis cinerea in laboratory experiments. The most effective of these was A. roseus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1975
1975
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Jo 1940-luvulla apilamädän tuhovoima alkoi laantua, koska erilaiset apilamädän rihmastopahkoissa loisivat sienet (esim. Coniothyrium minitans ja Episclerotium sclerotiorum) alkoivat luontaisesti yleistyä apilapelloilla (Erviö 1965). Myös viimeaikaiset selvitykset (Yli-Mattila ym.…”
Section: Kasvitaudit Hallintaan Välikasveilla Ja Viljelytekniikallaunclassified
“…Jo 1940-luvulla apilamädän tuhovoima alkoi laantua, koska erilaiset apilamädän rihmastopahkoissa loisivat sienet (esim. Coniothyrium minitans ja Episclerotium sclerotiorum) alkoivat luontaisesti yleistyä apilapelloilla (Erviö 1965). Myös viimeaikaiset selvitykset (Yli-Mattila ym.…”
Section: Kasvitaudit Hallintaan Välikasveilla Ja Viljelytekniikallaunclassified
“…de Bary by CAMPBELL (1947) in California and was subsequently shown to be parasitic on these sclerotia. Since that time there have been several reports of C. minitans parasitising sclerotia of 5. sclerotiorimi under natural conditions (ZUB 1960, ERVIO 1965, JONES and WAT-SON 1969, VoRos 1969, SCHMIDT 1970, HUANG 1977.…”
Section: Zusammenfassungmentioning
confidence: 99%
“…de Bary by CAMPBELL (1947) in California and was subsequently shown to be parasitic on these sclerotia. Since that time there have been several reports of C. minitans parasitising sclerotia of 5. sclerotiorimi under natural conditions (ZUB 1960, ERVIO 1965, JONES and WAT-SON 1969, VoRos 1969, SCHMIDT 1970, HUANG 1977.Although the importance of C. minitans as a potential biological control agent of sclerotium forming fungi has frequently been reported (TURNER and TRIBE 1975, AHMED and TRIBE 1977, HUANG 1980, TRUTMANN, KEANE and MERRIMAN 1980, 1982 relatively little work has been published regarding the actual nature of this parasitism. JONES, CORDON and BACON (1974) demonstrated that C. minitans produces /j-(l-^3)-glucanase enzymes which are responsible for the lysis of cell walls of S. sclerotiorum.…”
mentioning
confidence: 99%
“…C. minitans was discovered on sclerotia of S. sderotiorum m Cahfornia by Campbell (1947) and has since been found on that species in Hungary (Voros, 1969), Scotland (Jones and Watson, 1969) and East Germany (Schmidt, 1970). It has been found on S. trifoliorum in England (Tribe, 1957), Poland (Zub, 1960) and Finland (Ervio, 1965…”
Section: Introductionmentioning
confidence: 99%